Screening of Microorganisms Isolated from Stingless Bees' Larval Food in the Biocontrol of Meloidogyne incognita - Nunes Moreira Costa Guilherme; Santos Ana Carolina Costa; dos Santos Paschoal Tamires; Garcia Anna Paula Martins; dos Santos Anderson Rodrigues; Ueira-Vieira Carlos (Journal of Nematology, 2025)
The plant-parasitic nematode Meloidogyne incognita causes significant financial losses in agriculture due to its wide range of host plants. Microbe-based biological control is increasingly being recognized as a viable and environmentally sustainable alternative to synthetic chemical nematicides. With this in mind, the present study evaluated the potential of microorganisms found in the larval food of stingless bees for the biological control of M. incognita. Screening of these microorganisms revealed the presence of a bacterium with nematicidal activity against M. incognita. Pot tests with soybean plants demonstrated that the bacterium Mq-MCK-07 reduced the population of M. incognita, while in vitro tests confirmed its nematicidal effect on second-stage juveniles (J2) as well as its inhibitory effect on egg hatching. DNA sequencing identified the bacterium as Enterococcus faecalis strain mandacaium, and revealed potential genes of interest for the control of multiple pathogens. This study provides a theoretical foundation for E. faecalis strain mandacaium as a promising eco-friendly nematicide.